Komparace nezaměstnanosti v ČR dle jednotlivých krajů - Mikeš, Štěpán (Univerzita Pardubice, 2006)
Práce je zaměřena na komparaci nezaměstnanosti v jednotlivých krajích České republiky od roku 2000 do roku 2005. Pro komparaci byla použita metodika Ministerstva práce a sociálních věcí ČR a to míra registrované nezaměstnanosti zjišťované na základě statistik úřadů práce.

This work is concerning an unemployment comparison in Czech Republic according to particular regions from the year 2000 to 2005. For comparing was used methodics of Ministry of labour and social affairs, it means rate of registered unemployment investigated with Employment office.
Unemployment comparison in Czech republic according to particular regions
Keywords: Unemployment; comparison; regions; Nezaměstnanost; komparace; porovnání; kraje